2016
DOI: 10.1103/physrevb.94.054301
|View full text |Cite
|
Sign up to set email alerts
|

Transient phases and dynamical transitions in the post-quench evolution of the generalized Bose-Anderson model

Abstract: The exact description of the time evolution of open correlated quantum systems remains one of the major challenges of condensed matter theory, specially for asymptotic long times where most numerical methods fail. Here, the post-quench dynamics of the N-component Bose-Anderson impurity model is studied in the N → ∞ limit. The equilibrium phase diagram is similar to that of the Bose-Hubbard model in that it contains local versions of Mott and Bose phases. Using a numerically exact procedure we are able to study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…In order to understand this behaviour we proceeded as in the closed case and consider the quench to be a small perturbation δM/M (∞) 1, with δM = M (∞) − M eq , where M eq is the equilibrium value of the magnetization at U = U f . The solution of the equations of motion (12) is assumed to be of the form τ k (t) = τ k eq +s k (t), and M (t) = M eq − δ(t), where τ k eq is equilibrium value of pseudo-spin for U = U f . Expanding Eq.…”
Section: Open Systemmentioning
confidence: 99%
“…In order to understand this behaviour we proceeded as in the closed case and consider the quench to be a small perturbation δM/M (∞) 1, with δM = M (∞) − M eq , where M eq is the equilibrium value of the magnetization at U = U f . The solution of the equations of motion (12) is assumed to be of the form τ k (t) = τ k eq +s k (t), and M (t) = M eq − δ(t), where τ k eq is equilibrium value of pseudo-spin for U = U f . Expanding Eq.…”
Section: Open Systemmentioning
confidence: 99%
“…In our recent paper [20], we have shown that impurity models can exhibit dynamical phase transitions as well. We have studied the generalized Bose-Anderson model, in which N identical nonlinear oscillators are connected to the same lattice site.…”
mentioning
confidence: 96%
“…The equilibrium phase diagram of the model is shown in the lower panel of Figure 1. We study a type of quenches for which a dynamical transition was reported in [20]. They correspond to a sudden lowering −ε 0 within the lBEC domain for the system initially prepared in its ground state.…”
mentioning
confidence: 99%
See 2 more Smart Citations